Effect of hydrocolloids and wheat fiber on frozen sweet potato cakes with savoury coconut filling (kuih cucur badak) - Zainalabidin, Sriizzati Fatin; Karim, Roselina; Mohd Adzahan, Noranizan; Abdul Karim, Muhammad Shahrim; Mahyudin, Nor Ainy (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2013)
Kuih Cucur badak (CB) is a Malaysian traditional cake that uses sweet potato (Ipomoea batatas) as the main ingredient. Sweet potato dough that was filled with savoury coconut filling was fried before consumption. As the preparation of this cake is tedious and time-consuming, of these products into frozen form for bulk storage can be of advantage. However, frozen foods usually will undergo changes and damage in terms of shape, texture and flavor during the freezing process and frozen storage. From previous studies, hydrocolloid and fiber were found to be able to minimize negative effects of the freezing on starch based products. Therefore, the aim of this project was to investigate the effect of addition of different types of hydrocolloids (arabic gum, karaya gum and locust bean gum) and wheat fiber on the quality of CB. Quality characteristics evaluated were moisture content, oil absorption, drip loss, water activity, texture profile analysis (TPA) and sensory acceptability. In general, result showed that addition of hydrocolloids and fiber had significantly (p≤0.05) influenced the moisture content, fat content, water activity and texture profile analysis of the frozen CB. However, no significant (p<0.05) effect was observed on sensory evaluation since the amount used is in a very low percentage (0.1-0.5%).